The Multi-Messenger Approach to High-Energy Gamma-Ray Sources Third Workshop on the Nature of Unidentified High-Energy Sources - Paredes, Josep M.; Reimer, Olaf; Torres, Diego F. (Springer Netherlands : Imprint: Springer, 2007)
This book provides a theoretical and observational overview of the state of the art of gamma-ray astrophysics, and their impact and connection with the physics of cosmic rays and neutrinos. With the aim of shedding new and fresh light on the problem of the nature of the gamma-ray sources, particularly those yet unidentified, this book summarizes contributions to a workshop that continues with the series initiated by the meeting held at Tonantzintla in October 2000, and Hong-Kong in May 2004. This books will be of interest for all active researchers in the field of high energy astrophysics and astroparticle physics, as well as for graduate students entering into the subject.